The Effect of Sweet Orange (Citrus sp) Cultivation on Increasing Farmers' Income in Partibi Lama Village, Merek District, Karo Regency - Lingga, Silvia Wardana Br; Fadlan, Ahmad; Ramadhan, Anggia (EDUCTUM: Journal Research, 2025)
This study aims to examine the factors that influence farmers’ income from sweet orange farming in Partibi Lama Village, Merek District. The research utilizes primary data obtained through direct interviews with sweet orange farmers by distributing questionnaires. This is a quantitative study applying Confirmatory Factor Analysis (CFA), followed by Path Analysis using SPSS version 25. The CFA results indicate that two variables—Production and Land Area—are significantly associated with farmers' income in the study area. Furthermore, the path analysis shows that: (1) Land and Pesticides have a direct, positive, and significant effect on sweet orange production; (2) Land, Pesticides, and Production directly and significantly influence farmers' income; and (3) Land and Pesticides indirectly affect income through the mediating role of Production.